Organizational Effectiveness in Educational Institutions - Jacob, Namitha Elizabeth; Shari, Baby (EDUCARE, 2013)
ABSTRACT: Organizational effectiveness is a concept of how effective an organization is in achieving the outcomes the organizations intends to produce. Every organization regardless of industry or country seeks to be more effective and achieve superior results. Academic organizations are not less different. The public at large has become more conscious of its institutions of higher education. And universities, as a part of its main objective, conduct several studies for the societal benefits. However, there are a very few studies conducted on these institutions themselves, even though a part of the national budget is set aside for the development of societal reforming organizations like schools and universities. In other words, though a widely used and researched area, there still exists a lack of clarity with regard to the general understanding of organizational effectiveness and this goes true for academic institutions as well. The system of education needs to conduct its own research into the identification of the variables and factors associated with effectiveness. However, the meaning of the effectiveness of an educational institution is defined as its successful operation in terms of awareness of the organizational missions by the administrator, faculty members, and the support staff. This paper attempts to understand the basis of attaining effectiveness in academic institutions and also attempts to reflect on the ways in which effectiveness can be enhanced. Finally, no single model accurately describes the conditions in an institution, instead multiple models provide a richer understanding of organizational outcomes.KEY WORDS: Organizational effectiveness, academic organizations, organized anarchy, students, faculty members, administrators, and universities.===About the Authors: Namitha Elizabeth Jacob is a Research Scholar at the Department of Psychology, University of Calicut, Kerala, India; and Dr. Baby Shari is a Reader at the same Department, University of Calicut, Kerala, India. The authors can be contacted via e-mail at: namithaej@gmail.comHow to cite this article? Jacob, Namitha Elizabeth & Baby Shari. (2013). âOrganizational Effectiveness in Educational Institutionsâ in EDUCARE: International Journal for Educational Studies, Vol.6(1) August, pp.17-26. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 17, 2013); Revised (July 19, 2013); and Published (August 17, 2013).Â Â